Rewrite the equation as <math><mstyle displaystyle="true"><mfrac><mrow><mi>h</mi><mrow><mo>(</mo><mi>a</mi><mo>+</mo><mi>b</mi><mo>)</mo></mrow></mrow><mrow><mn>2</mn></mrow></mfrac><mo>=</mo><mi>A</mi></mstyle></math> .

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mn>2</mn><mfrac><mrow><mi>h</mi><mrow><mo>(</mo><mi>a</mi><mo>+</mo><mi>b</mi><mo>)</mo></mrow></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Apply the distributive property.

Subtract <math><mstyle displaystyle="true"><mi>h</mi><mi>a</mi></mstyle></math> from both sides of the equation.

Divide each term in <math><mstyle displaystyle="true"><mi>h</mi><mi>b</mi><mo>=</mo><mn>2</mn><mi>A</mi><mo>-</mo><mi>h</mi><mi>a</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>h</mi></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>h</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Simplify each term.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>h</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn><mi>a</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Rewrite <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn><mi>a</mi></mstyle></math> as <math><mstyle displaystyle="true"><mo>-</mo><mi>a</mi></mstyle></math> .

Do you know how to Solve for b A=(h(a+b))/2? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.